Comparison of severely ill patients with influenza A(H1N1)pdm09 infection during the pandemic and post-pandemic periods in Singapore. Issue 5 (29th January 2015) - Lim, Cindy; Ang, Li Wei; Ma, Stefan; Lai, Florence Yuk Lin; James, Lyn; Cutter, Jeffery
Highlights We compared severely ill patients during pandemic and post-pandemic periods. Severely ill patients were significantly older in the late post-pandemic period. Significantly more patients died in the late post-pandemic period. Older age was significantly associated with mortality.